Description of a new species of Microcerella (Diptera: Sarcophagidae) from Argentinean Patagonia - Mariluis, Juan C. (Zootaxa, 2006)
Microcerella coniceti sp. nov. is described and illustrated from Santa Cruz province, Argentina, based on male specimens. A new record of Microcerella curicoensis (Lopes) from Austral Argentinean Patagonia is provided.